2014
DOI: 10.1111/bph.12419
|View full text |Cite
|
Sign up to set email alerts
|

Midkine as a regulator of B cell survival in health and disease

Abstract: In healthy individuals, the pool of peripheral lymphocytes is constant in size. The control of lymphoid homeostasis is the result of a very fine balance between lymphocyte production, survival and proliferation. Survival factors have been shown to play a critical role in maintaining the correct size of lymphocyte populations. Midkine, a heparin-binding cytokine was recently shown to be involved in cell proliferation, differentiation and apoptosis in various cell types including normal and malignant B cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 89 publications
(120 reference statements)
1
7
0
Order By: Relevance
“…In addition, MK has also been demonstrated to serve as a regulator of mature B-cell survival in B-cell lymphoma. 48 In the present study, Mdk À/À mice did not show any immune-complex deposition in subepithelial areas, which was previously reported. 49 MK may affect humoral immunity through activation of T cells in TMPD-induced LN.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, MK has also been demonstrated to serve as a regulator of mature B-cell survival in B-cell lymphoma. 48 In the present study, Mdk À/À mice did not show any immune-complex deposition in subepithelial areas, which was previously reported. 49 MK may affect humoral immunity through activation of T cells in TMPD-induced LN.…”
Section: Discussionsupporting
confidence: 86%
“…It has been established that immune signalling contributes significantly to changes in the rewarding pathways of the brain induced by drugs of abuse [28], suggesting that endogenous modulators of immune response could be considered as novel pharmacological targets in addictive disorders. Very interestingly, MK is a known regulator of innate immune response [29]. MK is known to modulate expression of proinflammatory cytokines and the expansion of regulatory T-cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…We also previously observed that FSTL3 is elevated, compared to healthy controls, in the sera, PBMCs, and skin of patients with dcSSc [ 28 ]. The growth factor, MDK, has been implicated in the pathogenesis of hypertension, kidney disease, and lung fibrosis [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%